Ask the Specialist podcast: Larrakia, Tiwi and Yolngu stories to inspire better healthcare: Presenter(s): Vicki Kerrigan, Charles Darwin University, Australia; Stuart Yiwarr McGrath, Charles Darwin University, Australia. (April 2023) - Herdman, Rarrtjiwuy Melanie; Puruntatameri, Pirrawayingi; Lee, Bilawara; Cass, Alan; Ralph, Anna; Hefler, Marita
Abstract : Background: In Australia's north, poor intercultural communication is a common way Aboriginal patients experience racism and has resulted in death. At Royal Darwin Hospital, >70% of patients identify as Aboriginal, and most healthcare providers are non-Indigenous. To assist providers deliver respectful care they are offered Aboriginal cultural awareness training: this is despite critiques globally that such training reinforces negative stereotypes. As an alternative there is momentum around cultural safety training which requires healthcare providers to develop critical consciousness. However, there is a paucity of evidence that cultural safety can achieve its intended outcomes to address racism in healthcare. Methods: We developed and evaluated a cultural education podcast: Ask the Specialist: Larrakia, Tiwi and Yolŋu stories to inspire better healthcare. We produced 7 x<18 minute episodes in which doctors ask Aboriginal leaders, known as the "Specialists", questions about working with Aboriginal patients. The aim was to deliver cultural education in a flexible, concentrated format which promotes critical self-reflection. To evaluate the podcast, doctors listened to one episode per week over 7 weeks (29/1/20 -11/3/20) and provided feedback through weekly written reflections and an interview after listening to all 7 episodes. Findings: Doctors reported attitudinal and behavioural changes which indicated the development of critical consciousness. Doctors changed behaviour in relation to building rapport with patients, asking patients questions, working with Aboriginal interpreters, and gaining informed consent. Doctors also reflected on long-held stereotypes and the everyday nature of racism. Discussion: Cultural education, which addresses the problems doctors face, delivers "counterstories" from Aboriginal peoples, and encourages critical consciousness can counter racist narratives in healthcare. The podcast format was rated highly by doctors who appreciated the 7-week program which allowed for cycles of listening, reflection, and action. While the podcast was purposefully local, issues raised had applicability beyond the NT and outside of healthcare.